Xanthochroina Ganglbauer, 1881, a new genus of Oedemeridae for the Italian fauna (Coleoptera) - Bologna, Marco A.; Badano, Davide; Poloni, Riccardo (Fragmenta entomologica, 2020)
In this paper is reported for the first time with certainty the presence in Italy of the genus Xanthochroina, exhibiting a Holarctic discontinuous distribution. The Mediterranean species X. auberti is recorded from western Liguria and information on the range of the species is updated.